Embracing maqasid al-shariah and sustainable development goals in takaful business - Nuraisyah Ibrahim; Ruzian Markom (Penerbit Universiti Kebangsaan Malaysia, 2024)
Takaful, as an Islamic alternative to conventional insurance, has garnered significant attention due to its foundation in cooperation, mutual assistance, and Shariah compliance. This unique model is not only aligned with Islamic principles but is also seen as contributing to global financial security. Beyond its immediate financial benefits, takaful is increasingly recognized for its potential to support broader social and environmental objectives, including those outlined in the United Nations' Sustainable Development Goals (SDGs). The principles of takaful, particularly in terms of wealth protection and risk-sharing, resonate strongly with the goals of poverty reduction, responsible consumption, and social equity advocated by the SDGs. This article delves into a comparative analysis of the maqasid al-Shariah (objectives of Islamic law) and the SDGs, exploring their synergies and areas of potential integration within the takaful business framework. Both frameworks emphasize ethical values, social justice, and the promotion of well-being, making them highly compatible. The study adopts a qualitative research approach, utilizing doctrinal methods based on comprehensive library research and document analysis. The findings reveal that maqasid al-Shariah and the SDGs are complementary in their objectives, with both contributing to a more sustainable and ethical takaful industry. The article concludes with recommendations for integrating these two frameworks to enhance the higher objectives of Shariah in the takaful business. Such integration could foster a more holistic approach to financial services, ensuring that takaful not only meets Shariah requirements but also contributes to global efforts towards sustainability and social justice.